Work environment for hospital nurses in Japan: The relationships between nurses' perceptions of their work environment and nursing outcomes - Yasuko Ogata; Kana Sato; Yoshimi Kodama; Noriko Morioka; Kikuko Taketomi; Yuki Yonekura; Kimiko Katsuyama; Sachiko Tanaka; Midori Nagano; Yoichi M. Ito; Katsuya Kanda; the rest of the WENS‐J project team (Wiley, 2021)
Abstract Aim To investigate nurses' perceptions of their work environment and to investigate the relationships between variables measuring the work environment (WE) and nursing outcomes (NOs). Design A 2‐year prospective longitudinal survey (2013-2015). Method(s) Descriptive statistics of nurse demographics, organizational WE and NOs were calculated by position. The associations between Practice Environment Scale of the Nursing Work Index (PES‐NWI) and NOs were examined for each unit. Results The participants were 2,992 staff nurses, 137 nurse managers (NMs), and 8 chief nursing officers in Phase 1 and 7,849, 371 and 23 in Phase 2, respectively. The higher the job position, the better the WE was rated. The higher the PES‐NWI scores, the better the outcomes. Descriptive statistics about organizational WEs and NOs and the statistically significant associations between the two were identified.